(untitled) (Computer systems and information technologies, 2024)
Current research builds on an investigation of skeletal animation methods, focusing on the use of control points for managing limb movements. It thoroughly considers the relevance and significance of the chosen topic and its impact on creating realistic and effective visual projects in the modern world of digital graphics and reproduction. The research includes an analysis of the impact of sample quantity on the frame transitions smoothness and the rendering time to achieve a balance between quality and efficiency. It also involves refining the method through adaptation for execution on a GPU graphic processor. Studied Blender 3D engines (EEEVE and Cycles) allowed to analyze rendering performance on different computational architectures – CPU and GPU depending on sample values (60 and 128), frame number (250, 500, and 1000), and also the frame frequency at a rate of 30 frames per second. The goal of the research was an achievement of optimal balance between performance and realism in animation details reproduction. Three experiments were done to reach this goal and make the following conclusion: graphical processor utilization through the Cycles engine demonstrated a rendering acceleration of 43%, ranging from minimal to maximum settings. In the same time, the acceleration of the hybrid system via the EEVEE engine showed an acceleration of 15.2% only.